Pragmatic Analisis of the Song Lyric 'Lonely' By Justin Bieber : a Case Study on Implicature - Mustakim Mustakim; Joko Wibowo (International Journal on Advanced Science, Education, and Religion, 2026)
Music is one of the tools used by musicians to express a feeling through the lyrics of the songs they make, either directly or through implied messages. in this study which aims to analyze the song “lonely” by justin beiber through a pragmatic approach, more precisely on the disclosure of implicature. In the lyrics of this song, there are many implied messages that are not expressed directly but through implicatures that reflect the sense of alienation and deep loneliness experienced by the singer in his personal life, therefore this study aims to reveal what he really wants to convey through the lyrics of the song. In this study using a qualitative method with a pragmatic approach put forward by grice regarding conversational and conversational implicature. The results of this song reveal a deep sense of loneliness and isolation experienced personally by the publisher of this song. In this implicature research reveals through the use of implied messages in the lyrics of the song. Hopefully with the results of this study can provide a deeper understanding of what exactly wants to be conveyed through the language used to convey a psychological and emotional message in the context of popular song lyrics.